2020
DOI: 10.32479/irmm.9715
|View full text |Cite
|
Sign up to set email alerts
|

Linking Managerial Coaching With Employees’ Innovative Work Behaviors Through Affective Supervisory Commitment: Evidence From Pakistan

Abstract: Organizations in the era of globalization are promoting managerial coaching (MC) as human resource development practice to improve employees' outcomes in the workplace. The existing literature on manager coaching lacks the empirical studies showing the linking MC with attitudes and behaviors of employees. To fill the gap mentioned above, this study explores the direct linkage between the MC and innovative work behaviors (IWBs) of employees as well as an indirect relationship through the intervening role of aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
(47 reference statements)
3
17
0
1
Order By: Relevance
“…Therefore, the commitment of UFO Elektronika employees is very high so that they have high innovative thinking to participate in increasing the company's revenue (Marques et al, 2013). These results are in line with the research of Elshifa et al (2019), Ismail (2019, Tang et al (2019), Dahri (2018), Bak (2020), andAli et al (2020).…”
Section: The Effect Of Organizational Commitment On Innovative Work Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the commitment of UFO Elektronika employees is very high so that they have high innovative thinking to participate in increasing the company's revenue (Marques et al, 2013). These results are in line with the research of Elshifa et al (2019), Ismail (2019, Tang et al (2019), Dahri (2018), Bak (2020), andAli et al (2020).…”
Section: The Effect Of Organizational Commitment On Innovative Work Behaviorsupporting
confidence: 91%
“…A series of innovation processes requires several employees who are committed to exchanging knowledge and creating a favorable atmosphere of innovation. Research conducted by Elshifa et al (2019), Ismail (2019), Tang et al (2019), Dahri (2018), Bak (2020), and Ali et al (2020) showed the results that the effect of organizational commitment on innovative work behavior was significantly positive. However, Serna et al (2018) stated that there was no effect on the relationship between organizational commitment and innovative work behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, DeRue et al (2010) claim that coaching empowers employees to decide about the approach to be used for the achievement of the desired outcomes which boosts employees' involvement in creative ideas' generation and implementation (Cheung and Wong, 2011). Ali et al (2020) focus on the importance of managerial coaching and its positive effect on employees' creativity in the software industry in Pakistan. They explain that when managers' conventional role is shifted and become coaches, the organisational culture changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studi ini mengevaluasi dua jalur; pengaruh langsung dan tidak langsung dari managerial coaching terhadap perilaku inovatif pegawai, yakni, pengaruh langsung managerial coaching terhadap perilaku inovatif pegawai, dan pengaruh tidak langsung managerial coaching terhadap perilaku inovatif pegawai melalui 4715 Manager as Coach: Ekskalasi Kinerja Pegawai melalui Managerial Coaching -Yunianto Agung Nugroho, Masduki Asbari, Firdaus Putra, Riyanto, Gusli (Ali et al, 2020). Temuan penelitian ini juga mengonfirmasi bahwa memiliki motivasi intrinsik yang besar memainkan peran penting sebagai mediator antara managerial coaching dan perilaku inovatif pegawai.…”
Section: Pembahasanunclassified